Interpersonal communication between parents and children from Hamka's perspective: A thematic study in the Tafsir Al-Azhar on Surah Luqman verses 16-19 - Affandi, Yuyun; Husna, Azzah Luqinatul; Alhuwaymil, Mohammed Saad (Islamic Communication Journal, 2024)
Interpersonal communication between parents and children is essential in the digital era. The role of parents and effectiveness in building communication must be implemented well. With its unique focus on Islamic values, this study aims to explore key elements in such communication. The research method used is library research with a qualitative research model on verses related to the story of Luqman in the Al-Qur’an, highlighting the interpretation of Buya Hamka in Tafsir Al-Azhar. The research results show firstly, in surah Luqman verses 16-19, it explains the amount of good that is done, the obligation to perform prayers, the obligation to amar ma’ruf against evil, the recommendation to be patient when experiencing misfortune, as well as morals and manners in interacting with fellow humans, such as not turning away, human face. Secondly, the interpersonal communication patterns of parents and children are contained in surah Luqman verses 16-19: equality and openness, empathy and positive behavior. This pattern can be demonstrated by various kinds of behavior and attitudes, including choosing the proper diction, making the child a speaking partner of the same age, and not looking away and not shouting at the child. With its unique Islamic perspective, the implication is that this study significantly enriches the treasures of interpersonal communication.*****Komunikasi interpersonal orang tua dan anak menjadi kajian penting di era digital. Peran orang tua dan efektivitas dalam membangun komunikasi perlu diterapkan dengan baik. Studi ini bertujuan untuk mengeksplorasi elemen-elemen kunci dalam komunikasi tersebut, menyoroti nilai-nilai Islami yang dapat diterapkan dalam konteks hubungan keluarga. Metode penelitian yang digunakan adalah library research dengan model penelitian kualitatif terhadap ayat-ayat yang terkait dengan kisah Luqman dalam Al-Qur’an, dengan menyorot penafsiran Buya Hamka dalam Tafsir Al-Azhar. Hasil penelitian menunjukkan pertama, bahwa Surah Luqman ayat 16-19 menerangkan tentang sebesar apapun kebaikan yang dikerjakan, kewajiban mendirikan shalat, kewajiban amar ma’ruf nahi munkar, anjuran bersabar ketika mendapat musibah, serta akhlak dan sopan santun dalam berinteraksi pada sesama manusia, seperti tidak memalingkan wajah dari manusia. Kedua, pola komunikasi interpersonal orang tua dan anak yang terdapat dalam Surah Luqman ayat 16-19, yaitu: kesetaraan dan keterbukaan, empati, dan perilaku positif. Pola tersebut dapat ditunjukkan dengan berbagai macam perilaku dan sikap, antara lain: pemilihan diksi yang tepat, menjadikan anak sebagai patner bicara yang seusia, dan tidak memalingkan wajah serta tidak berteriak kepada anak. Implikasinya, studi ini dapat memperkaya khazanah komunikasi interpersonal menurut perspektif keislaman.